Restitution and Compensation for Crime Victims: A Normative Shift in the Criminal Justice System - Andi Abid Rafly Hasanuddin; Syarif Saddam Rivanie; Muhammad Said Karim; Ismail Iskandar; Aditya Pratama Utomo (SIGn Journal of Social Science, 2026)
The national criminal justice system has undergone a normative shift from a retributive approach toward justice oriented to the recovery of victims’ rights through restitution and compensation. This normative development raises an issue of horizontal synchronization between Law Number 20 of 2025, as the general criminal procedure law that regulates the right to compensation conditionally where the offender is unable to fulfill restitution, and Law Number 3 of 2026, as a special law that limits compensation to certain categories of victims. This study aims to analyze that paradigm shift, evaluate the regulatory disharmony between the two laws, and formulate a prescriptive basis for state involvement in the recovery of victims’ rights. This study applies normative legal research using statute, historical, and conceptual approaches. The findings show that the limitation of compensation under the special law may create differentiated legal protection for crime victims outside those special categories where the offender is unable to fulfill restitution. Therefore, the obligation of investigators, public prosecutors, and judges to notify and facilitate the rights to restitution and compensation should be understood as an active state mandate to guarantee victims’ access to recovery. This study recommends harmonizing Law Number 3 of 2026 with Law Number 20 of 2025 and enacting a Government Regulation on the transparent and accountable governance of the endowment fund.